Establishment of a non-native xyleborine ambrosia beetle, Xyleborus monographus (Fabricius) (Coleoptera: Curculionidae: Scolytinae), new to North America in California - Rabaglia, Robert J.; Smith, Sheri L.; Rugman-Jones, Paul; Digirolomo, Marc F.; Ewing, Curtis; Eskalen, Akif (Zootaxa, 2020)
Specimens of an ambrosia beetle, Xyleborus monographus (Fabricius), were found infesting oak trees in California. This is the first record of this species established in North America. Based on collection information, this species most likely has been established in the Napa County area for several years. A modified key to Xyleborus in North America, and diagnosis of the species is provided.